Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/myc.13331
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of onychomycosis and nail psoriasis and its correlation with systemic treatment

Abstract: Background Epidemiological studies indicate that onychomycosis may affect up to 79% of psoriatic patients. Onychomycosis in psoriatic patients is more commonly caused by yeasts comparing with non‐psoriatic. Objectives Evaluate the prevalence of fungi in nail psoriasis. Evaluate the association between direct mycological examination (DME) and mycological culture, Nail Psoriasis Severity Index (NAPSI) and systemic treatment for psoriasis. Methods Of 133 nails from 20 patients with nail psoriasis were evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…The lower prevalence in patients using acitretin (8.3%), ustekinumab (20%), secukinumab (15.4%) compared to the untreated group (31.3%) was remarkable. In a few studies, it has been reported that the use of systemic therapy increases the risk of onychomycosis compared to the use of only topical therapy, but no significant data can be presented on the specific treatment agent 23,32 . Some studies have reported that methotrexate significantly slows nail growth 10 and increases the risk of onychomycosis 10,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower prevalence in patients using acitretin (8.3%), ustekinumab (20%), secukinumab (15.4%) compared to the untreated group (31.3%) was remarkable. In a few studies, it has been reported that the use of systemic therapy increases the risk of onychomycosis compared to the use of only topical therapy, but no significant data can be presented on the specific treatment agent 23,32 . Some studies have reported that methotrexate significantly slows nail growth 10 and increases the risk of onychomycosis 10,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies, it has been reported that the use of systemic therapy increases the risk of onychomycosis compared to the use of only topical therapy, but no significant data can be presented on the specific treatment agent. 23,32 Some studies have reported that methotrexate significantly slows nail growth 10 and increases the risk of onychomycosis. 10,33 In the study of Al-Mutairi et al patients who received etanercept, infliximab, adalimumab and those who did not receive any biologic agents were compared in terms of onychomycosis risk.…”
Section: Discussionmentioning
confidence: 99%
“…Whether psoriasis predisposes patients to super cial fungal infection remains controversial. The immunomodulatory effects of systemic treatments, microbiota dysbiosis of the skin and nails, and immunologic disturbance of capillary units are contributing factors, while the abundance of antimicrobial peptides and fast turnover of the skin and nails are inhibitory factors [1][2][3] . Previous meta-analyses or large cohort studies were limited to onychomycosis or mucocutaneous candidiasis 2,4,5 .…”
Section: Main Textmentioning
confidence: 99%
“…В различных исследованиях онихомикоз стоп у больных псориазом был выявлен в 21,5-90% случаев [6][7][8][9][10][11][12][13][14].…”
unclassified
“…К грибковому поражению ногтей у больных псориазом предрасполагают: длительность течения заболевания псориазом более 10 лет, распространенный кожный процесс, псориатический артрит, проведение системной иммуносупрессивной терапии, выраженные нарушения кровоснабжения конечностей [12][13][14].…”
unclassified